Zines And Computational Publishing Practices - Kendal Beynon (A Peer-Reviewed Journal About, 2024)
This paper explores the parallels between historical zine culture and contemporary DIY computational publishing practices, highlighting their roles as countercultural movements within their own right. Both mediums, from zines of the 1990s to personal homepages and feminist servers, provide spaces for identity formation, community building, and resistance against mainstream societal norms. Drawing on Stephen Duncombe's insights into zine culture, this research examines how these practices embody democratic, communal ideals and act as a rebuttal to mass consumerism and dominant media structures. The paper argues that personal homepages and web rings serve as digital analogues to zines, fostering participatory and grassroots networks and underscores the importance of these DIY practices in redefining production, labour, and the role of the individual within cultural and societal contexts, advocating for a more inclusive and participatory digital landscape. Through an examination of both zines and their digital counterparts, this research reveals their shared ethos of authenticity, creativity, and resistance.